2006
DOI: 10.1007/s10641-006-0041-1
|View full text |Cite
|
Sign up to set email alerts
|

Are fish populations in temperate streams affected by crayfish? – A field survey and prospects

Abstract: SynopsisFish populations may be affected by predation and competition from various types of organisms, among which crayfish have been suggested as important actors. We here present results from stream surveys, suggesting that neither native noble, Astacus astacus, nor introduced signal crayfish, Pacifastacus leniusculus, necessarily affect fish population densities in temperate stream communities. Comparisons of fish densities within stream sites between years with absence and presence of crayfish showed no ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 33 publications
2
28
1
1
Order By: Relevance
“…Hence the reduction in fish recorded in Bookill Gill Beck is most probably due to the high abundance and high biomass of signal crayfish. Degerman et al (2007) found no effect of signal crayfish on juvenile trout, even at high density of crayfish (25-100 crayfish·100 m −2 ) in electro-fishing catches. Electrofishing catches of crayfish are not directly comparable with trapping CPUE, but the sites in Bookill Gill Beck with the highest trapping CPUE also had the highest by-catches of crayfish in electrofishing, and these were greater than the highest densities recorded by Degerman et al (2007).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Hence the reduction in fish recorded in Bookill Gill Beck is most probably due to the high abundance and high biomass of signal crayfish. Degerman et al (2007) found no effect of signal crayfish on juvenile trout, even at high density of crayfish (25-100 crayfish·100 m −2 ) in electro-fishing catches. Electrofishing catches of crayfish are not directly comparable with trapping CPUE, but the sites in Bookill Gill Beck with the highest trapping CPUE also had the highest by-catches of crayfish in electrofishing, and these were greater than the highest densities recorded by Degerman et al (2007).…”
Section: Discussionmentioning
confidence: 75%
“…Stenroth and Nyström (2003) set up enclosures with signal crayfish and brown trout fry (Salmo trutta) in a Swedish stream, but found no effect of crayfish on the survival of the fish. Degerman et al (2007) reviewed data from electro-fishing surveys in 61 streams in southern Sweden that had a period of two years or more when indigenous noble crayfish Astacus astacus were present and another when crayfish were absent (generally losses due to crayfish plague), but did not find any reduction of abundance of fish related to either signal or noble crayfish in those streams. Where impacts of crayfish on fish do occur, they may be indirect through modification of aquatic food webs.…”
Section: Introductionmentioning
confidence: 99%
“…Appelberg et al (1993) showed that fish presence tends to induce behavioural responses among noble crayfish, causing them to remain in shelters throughout the day. Divergent effects of crayfish on fish have been reported; these may be highly dependent on the species and methods used, and the effects of crayfish on fish populations deserve further study to better understand community processes in streams (Degerman et al, 2007). In Scandinavia there is little evidence that native noble crayfish affect fish population densities in temperate stream communities (Stenroth and Nyström, 2003;Degerman et al, 2007).…”
Section: Interactions Between Indigenous Crayfish Species (Ics) and Fishmentioning
confidence: 99%
“…Divergent effects of crayfish on fish have been reported; these may be highly dependent on the species and methods used, and the effects of crayfish on fish populations deserve further study to better understand community processes in streams (Degerman et al, 2007). In Scandinavia there is little evidence that native noble crayfish affect fish population densities in temperate stream communities (Stenroth and Nyström, 2003;Degerman et al, 2007). In a long-term study of electro-fishing results in natural streams, comparisons of stream fish densities between years with absence or presence of crayfish in different densities showed no effect of native crayfish on fish.…”
Section: Interactions Between Indigenous Crayfish Species (Ics) and Fishmentioning
confidence: 99%
See 1 more Smart Citation